Antihaemophilic effect of vasopressin, deamino-(D-arginine8)-vasopressin and adrenaline in sheep: proposal for an in vivo assay system. - Heiniger, J. (1988)
Female sheep were used to assay antihaemophilic (factor VIII enhancing) activity of arginine vasopressin, deamino-(D-arginine8)-vasopressin (DDAVP) and adrenaline. The time course of the response was biphasic, two surges of factor VIII being observed. DDAVP was found to be the most potent of the substances investigated. Its optimal dose was 1 microgram kg-1 body wt (i.v.). It is suggested that a similar procedure can be employed to search for new peptides with anti-haemophilic action.